2021
DOI: 10.1002/app.51597
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of an organophosphorus compound on polypropylene‐g‐poly(glycidyl methacrylate) polymer support and its application in scandium recovery

Abstract: Scandium is a rare earth element that has a wide range of uses in modern technology. The conventional recovery of scandium is commonly done by solvent extraction using organophosphorus compounds. This process however produces a lot of waste extractants. To circumvent this challenge, a model organophosphorus compound phenylphosphinic acid (PPI) was immobilized to a polymer support fabric to produce a Sc(III) adsorbent for high throughput scandium recovery with less waste generation. Polymer support (PP-g-PGMA)f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…There are also discrete peaks at 890 and 830 cm −1 , which corresponded to asymmetric and symmetric oxirane ring bending/deformation, respectively ( Figure 1 ). [ 38 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also discrete peaks at 890 and 830 cm −1 , which corresponded to asymmetric and symmetric oxirane ring bending/deformation, respectively ( Figure 1 ). [ 38 ]…”
Section: Resultsmentioning
confidence: 99%
“…There are also discrete peaks at 890 and 830 cm −1 , which corresponded to asymmetric and symmetric oxirane ring bending/deformation, respectively (Figure 1). [38] Quantitative determination of copolymer composition was done using Proton Nuclear Magnetic Resonance ( 1 H NMR). With respect to the Myr, literature suggests poly(Myr) has varying regioselectivity (Figure S2, Supporting Information).…”
Section: Effect Of Feed Composition On My/gma Copolymerizationmentioning
confidence: 99%
“…Based on the 3D FTIR spectrum ( Figure 3 ) and the spectra extracted at maximum degradation temperatures ( Figure 4 A), it can be concluded that the depolymerization occurs at the beginning of poly(GMA- co -1,4DMB) microsphere decay and is followed by isomerization in the gas phase. The FTIR spectrum of gases gathered at 269 °C reveals the following bands: bands at 3059 cm −1 associated with vibrations of the methylene group in the oxirane ring [ 39 ]; bands at 1737 cm −1 from the vibrations of the C=O group in esters [ 40 ]; bands at 1650 cm −1 associated with vibrations of the C=C bond of the methacrylate group; bands at 1158 cm −1 related to vibrations of the C-O-C group in esters; bands at 939 cm −1 derived from vibrations of the =CH 2 group; bands at 842 cm −1 due to vibrations of the oxirane ring [ 41 ]. These bands are characteristic of GMA monomer [ 42 ] and their presence testifies that depolymerization takes place at the beginning of the decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…The spectra of the initial copolymer and the samples heated to higher temperatures are shown in Figure 4 B. The disappearance of the bands at 846 and 907 cm −1 derived from the vibrations of the oxirane ring can be observed in the spectrum of the sample heated to 265 °C, compared to the initial spectrum [ 41 ]. Furthermore, a band at 1255 cm −1 representing the stretching vibrations of the oxirane group also disappears [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation